Bahasa Inggris - Putri Wijayati, Hilda; Yuliani Rahayu, Endang (BASIS (Bahasa dan Sastra Inggris), 2025)
This study aims to examine the use of figurative language in three songs from Taylor Swift’s Evermore album: “Willow,” “Champagne Problems,” and “Gold Rush.” Figurative language is a crucial element in song lyrics, enabling artists to express emotions and abstract ideas creatively. The study applies Perrine’s theory, which classifies figurative language into five types: simile, metaphor, personification, hyperbole, and irony. The data are taken from the official lyrics of the selected songs, supported by repeated listening to capture emotional and contextual nuances. A qualitative descriptive method is used to identify and analyze instances of figurative language. The analysis focuses on how these figures of speech function in expressing emotional depth, storytelling, and thematic complexity. The findings reveal that metaphor and personification are the most dominant types, indicating Taylor Swift’s tendency to convey feelings through implicit comparison and human-like expressions. The study highlights the artistic and literary value of popular song lyrics, affirming that they can be treated as modern poetic texts worthy of academic analysis.